From Participation to Inclusive Forest Governance in REDD+ in the DRC - Kengoum, F.; Pham Thu Thuy; Mihigo, B-P.N. (CIFOR-ICRAF, 2022)
Stakeholder participation in natural resource management, and REDD+ in particular, are mandatory in the existing DRC legal frameworks. The key limitations to stakeholder participation in REDD+ are weak law enforcement, poor coordination, lack of financial resources, limited recognition of land and forest tenure, limited capacity, and insufficient monitoring and guidance at lower levels to ensure participation.